Financial constraints, R&D investment and productivity in U.S. manufacturing firms - zheng, Jing (2016)
The renewed attention to the linkages among financial constraints, R&D spending and innovative performance has been generated by the economic downturn and productivity growth deceleration noted in many of the industrialised countries. This paper contributes to a growing, but still incomplete, literature related to these issues, making use of 144 listed U.S manufacturing firms over the period from 2008 to 2014. There are three main findings: firstly, external equity financing is only found to have significant effect on financing R&D investment in mature firms; secondly, cash holdings have consistently significant impacts on R&D smoothing, especially in financially constrained firms; lastly, financially constrained firms (young and low dividend pay-out firms) tend to have higher output-R&D elasticity than unconstrained firms (large firms) and cash holdings negatively moderate the firms’ output-R&D elasticity. These findings demonstrate significant linkages between firm’s real investment decisions and corporate liquidity. They also provide a number of related insights, especially the moderating effect of corporate liquidity in input-output model at the firm level.